2020
DOI: 10.1039/c9cy01519a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of surface basic sites of catalysts in CO2 activation in dry reforming of methane: a short review

Abstract: Surface oxygen basic sites are vital to the CO2 activation in dry reforming of methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 62 publications
1
85
0
Order By: Relevance
“…Generally, the desorption of carbon dioxide at temperatures below 200 °C can be ascribed to a weak basicity, this being the case of the 5Ni9Ce‐ and 10Ni9Ce/SBA‐15 samples which show a main peak at 175 °C and a secondary one at 90 °C. In addition to the peaks at low temperature, the 10Ni18Ce/SBA‐15 exhibits a main peak at 260 °C with a wide shoulder up to 450 °C associated to the decomposition of carbonate species in moderate basic sites [52] which is also present in 5Ni9Ce/SBA‐15. Taking into account the relative intensity of the peaks and total adsorption of CO 2 , the order in basicity can be stablished as 10Ni18Ce‐ (17.6 μmol g −1 ) >5Ni9Ce− (16.0 μmol g −1 ) >10Ni9Ce− (7.9 μmol g −1 )≫5Ni‐≈10Ni/SBA‐15 (>1 μmol g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the desorption of carbon dioxide at temperatures below 200 °C can be ascribed to a weak basicity, this being the case of the 5Ni9Ce‐ and 10Ni9Ce/SBA‐15 samples which show a main peak at 175 °C and a secondary one at 90 °C. In addition to the peaks at low temperature, the 10Ni18Ce/SBA‐15 exhibits a main peak at 260 °C with a wide shoulder up to 450 °C associated to the decomposition of carbonate species in moderate basic sites [52] which is also present in 5Ni9Ce/SBA‐15. Taking into account the relative intensity of the peaks and total adsorption of CO 2 , the order in basicity can be stablished as 10Ni18Ce‐ (17.6 μmol g −1 ) >5Ni9Ce− (16.0 μmol g −1 ) >10Ni9Ce− (7.9 μmol g −1 )≫5Ni‐≈10Ni/SBA‐15 (>1 μmol g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…12 Reduction of carbon dioxide to carbon monoxide can be achieved by a variety of methods including electrochemically, 13 photochemically, 14 plasmatically 15 and thermally in processes such as the dry reforming of methane. 16 The carbon monoxide can then be combined with hydrogen in a Fischer-Tropsch reaction 17 to produce liquid hydrocarbons suitable for use as liquid transport fuels. This is a well-established commercial process.…”
Section: Carbon Dioxide Generation and Utilisationmentioning
confidence: 99%
“…CuCeZr showed the best activity and durability among the tested catalysts [17]. Lastly, Aziz and co-workers [18] reported that the coke could be removed by the gasification, and it could be enhanced by the basic site of the catalyst. C2H5OH + CO2 → 3CO + 3H2 (△H298K = + 296.7 kJ mol −1 )…”
Section: Introductionmentioning
confidence: 94%